Colorectal Cancer Screening in Rural and Urban Primary Care Practices Amid Implementation of the Medicare Access and CHIP Reauthorization Act - Tyrone F. Borders; Zachary J. Morgan; Lars E. Peterson (SAGE Publishing, 2023)
Purpose: The Medicare Access and CHIP Reauthorization Act (MACRA) incentivized primary care practices to improve colorectal cancer screening rates. This study examined if colorectal screening rates improved among rural and urban primary care practices amid implementation of MACRA. Methods: Colorectal cancer screening data are from a national registry of 139 primary care practices. Repeated measures regression tested for rural/urban differences and changes in screening rates between 2016 and 2020, adjusting for county demographic factors and social deprivation. Results: Screening rates were 64% in both rural and urban practices in the first quarter of 2016 and increased to 80% and 83% in rural and urban practices, respectively, in the last quarter of 2020. In adjusted analyses, screening rates increased by 4% per year and there were no rural/urban differences. Lower screening rates were associated with higher county proportions of persons who were 45 to 74 years of age and Hispanic. Higher screening rates were associated with higher county proportions of persons who were White, Black, and Asian and higher social deprivation. Conclusions: Colorectal screening rates improved among rural and urban primary care practices during implementation of MACRA, but disparities persist among practices serving county populations that are relatively older, more Hispanic, and have higher social deprivation.